Continuous 24-h Photoplethysmogram Monitoring Enables Detection of Atrial Fibrillation - Väliaho, Eemu-Samuli; Lipponen, Jukka A.; Kuoppa, Pekka; Martikainen, Tero J.; Jäntti, Helena; Rissanen, Tuomas T.; Castrén, Maaret; Halonen, Jari; Tarvainen, Mika P.; Laitinen, Tiina M.; Laitinen, Tomi P.; Santala, Onni E.; et al. (Frontiers in Physiology, 2022)
Aim Atrial fibrillation (AF) detection is challenging because it is often asymptomatic and paroxysmal. We evaluated continuous photoplethysmogram (PPG) for signal quality and detection of AF. Methods PPGs were recorded using a wrist-band device in 173 patients (76 AF, 97 sinus rhythm, SR) for 24 hours. Simultaneously recorded 3-lead ambulatory ECG served as control. The recordings were split into 10-, 20-, 30- and 60-minute time-frames. The sensitivity, specificity and F1-score of AF detection were evaluated for each time-frame. AF alarms were generated to simulate continuous AF monitoring. Sensitivities, specificities, and positive predictive values (PPVs) of the alarms were evaluated. User experiences of PPG and ECG recordings were assessed. The study was registered in the Clinical Trials database (NCT03507335). Results The quality of PPG signal was better during night-time than in daytime (67.3 ± 22.4% vs. 30.5 ± 19.4%, p<0.001). The 30-minute time-frame yielded the highest F1-score (0.9536), identifying AF correctly in 72/76 AF patients (sensitivity 94.7%), only 3/97 SR patients receiving a false AF diagnosis (specificity 96.9%). The sensitivity and PPV of the simulated AF alarms were 78.2% and 97.2% at night, and 49.3% and 97.0% during the daytime. 82% of patients were willing to use the device at home. Conclusion PPG wrist-band provided reliable AF identification both during daytime and night-time. The PPG data’s quality was better at night. The positive user experience suggests that wearable PPG devices could be feasible for continuous rhythm monitoring.